2006
DOI: 10.1007/s11154-006-9003-3
|View full text |Cite
|
Sign up to set email alerts
|

Diseases of Wnt signaling

Abstract: The Wnt signaling pathways play fundamental roles in the differentiation, proliferation, death and function of many cells and as a result are involved in critical developmental, growth and homeostatic processes in animals. There are four currently known pathways of Wnt signaling; the so-called canonical or Wnt/β-catenin pathway, the Wnt/Ca +2 pathway involving Protein Kinase A, the planar cell polarity pathway and a pathway involving Protein Kinase C that functions in muscle myogenesis. The best studied of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(76 citation statements)
references
References 96 publications
1
74
0
1
Order By: Relevance
“…[1][2][3][4]17 Controlling the differentiation of these cells may, therefore, represent a strategy to treat these diseases. The results presented herein suggest that the inappropriate activation of Wnt signaling drives the chondrogenic differentiation of progenitor cells present in the walls of blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4]17 Controlling the differentiation of these cells may, therefore, represent a strategy to treat these diseases. The results presented herein suggest that the inappropriate activation of Wnt signaling drives the chondrogenic differentiation of progenitor cells present in the walls of blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…1,3 Mounting evidence suggests that canonical Wnt signaling is central to normal skeletogenesis [4][5][6] and cancer-related bone diseases. 7,8 The first direct evidence of a role for Wnt signaling in human bone formation came from observations that inactivating mutations of the LRP5 gene, a coreceptor for Wnt, causes a syndrome associated with early-onset osteoporosis. 9 Subsequently, it was shown that a separate and distinct mutation in the same gene results in high bone density.…”
Section: Introductionmentioning
confidence: 99%
“…Esta via é ativada pela interação da glicoproteína WNT com seu receptor, formado pela junção da proteína Frizzled com proteínas da família LRP (low-density lipoprotein receptor-related protein), o que gera o acúmulo da proteína beta-catenina (também conhecida como CTNNB1) (JOHNSON; RAJAMANNAN, 2006). Uma vez livre, a Beta-catenina migra para o núcleo, onde interage com os fatores de transcrição como LEF (Lymphoid enhancer fator) (BEHRENS et al, 1996) …”
Section: Via Wingless (Wnt)unclassified